Foreign exchange intervention when interest rates are zero: Does the portfolio balance channel matter after all? - Rasmus Fatum (University of California, Santa Cruz Institute for International Economics (SCIIE), 2010)
The Japanese zero-interest rate period provides a 'natural experiment' for investigating the effectiveness and transmission channels of sterilized intervention when traditional monetary policy options are constrained. This paper takes advantage of the fact that all interventions in the JPY/USD market during the zero-interest rate period are sterilized sales of JPY and, therefore, none of these interventions can signal a future interest rate decrease. In order to further assess through which transmission channel these interventions work, the analysis integrates official daily Japanese intervention data with a comprehensive set of rumors data that capture interventions of which the market is aware. Market awareness is a necessary condition for intervention to disseminate information and work through channels other than the portfolio balance channel. The results of the time series analysis show that intervention, on average, induces a statistically and economically significant same-day depreciation of the JPY. Market awareness is shown to be unimportant. Consequently, the effects of Japanese interventions during the zero-interest rate period are consistent only with the portfolio balance channel. This is a remarkable finding, demonstrating that sterilized intervention is, in principle, an independent policy instrument.
Keywords: E52; F31; G14; 330; Exchange Rates; Foreign Exchange Market Intervention; Channels of Transmission